Growth patterns of subaqueous depositional channel lobe systems developed over a basement with a downdip break in slope: Laboratory experiments - Fernandez, Rocio Luz (2014)
A series of large-scale experiments on nonchannelized, depositional turbidity currents show the evolution and complex stratigraphy of channel-lobe systems developed updip and downdip of a break in slope. Two different sets of experimental turbidity currents with different sediment concentrations were run. The results provided a comparative picture of the gross structure of the fans, with information on their surfaces, growth sequences, and times of activity of the incised channels and lobed features. In particular, data analysis focused on: (a) velocity and suspended-sediment concentration of the flows themselves; (b) time and spatial sequences of channel and lobe construction and modification, and (c) spatial trends in grain-size distribution along the deposit. Significantly, the floor geometry employed in this study allowed investigation of adjustments in deep-sea fan deposition associated with natural changes in bed slope. We show here that the break in slope played a very important role in governing channel aggradation and lobe architecture over the deposit. More specifically, the slope break tended to break up the formation of long channels and enhance the formation of lobate features. A comparison with field submarine lobe analogs demonstrates that the morphodynamics and stratigraphy associated with lobed fans can indeed be modeled, within limits, at laboratory scale.